Strindberg och turismen: Resande, visuell kultur och skrivande i turismens tidsålder - Marcus, Gustaf (Tidskrift för litteraturvetenskap, 2020)
Strindberg and Tourism: Travelling, Visual Culture, and Writing in the Age of Tourism This article looks at August Strindberg’s travelogues from Italy (1884-1888) as a reaction to the early tourism industry at the end of the 19th century. The travelogues engage with the contemporary practices of mediating and representing tourist sites, including guidebooks, travel writing, and visual attractions, such as panoramas and dioramas. Following Jonathan Crary’s theory of modernist painting as a reaction to the malleability of visual perception, this study shows how the attempts to control, mediate, and disseminate impressions from tourist sites at the same time made them subjective and volatile. Thus, the tourist site and the tourist experience became an important point of departure for Strindberg’s literary experimentation. Keywords: , , ,